VALUASI EKONOMI LINGKUNGAN AKIBAT ALIH FUNGSI LAHAN PERTANIAN (Suatu Kasus di Kota Tasikmalaya, Jawa Barat) - Yolanda Erfrissadona; Lies Sulistyowati; Iwan Setiawan (University of Jember, 2020)
Economic growth and urbanization are increasing the demand for land affecting on the numerous conversion agricultural land. The conversion has bad impacts on the deprivation of the environmental service value. Economic valuation methods using WTA and WTP were applied to calculate the environmental service value produced by agricultural land. The purposes of the research are to calculate the environmental services value which is lost due to the impact of the conversion of agricultural land to non-agricultural land. The quantitative method using cluster random sampling technique was applied to analyze 206 respondents included in this research. The multiple linear analysis methods were used as the analytical method. The results show that there is a potential loss of economic value of Rp. 1.236.659.406 per year from environmental services as a reward for farmers who are willing to cultivate agricultural land which is calculated from WTA value and potential loss of WTP of Rp. 278.820.122 per year. Education, experience, land area, and income are the factors that influence the value of WTA in Purbaratu, Tasikmalaya. Furthermore, land area, fertilizer needs, seed requirements, and income are the factors that influence the value of WTP in Purbaratu, Tasikmalaya city. Keywords: land conversion, Willingness to Accept (WTA), Willingness to Pay (WTP)